(3JaSjQ GdYTGHs - (3CMeO Hf eMeO Hf eaQL GdCehj CHh GdYHGS GdfHGJj GdYTGH, GHf GdQhejI,J (B637 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ ShQI (B" (3GdCMbGa(B" s
(3BNQgG (B:s
(3hjfJgi HBNQ ShQI (B" (3GdJMQje (B" s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B218s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B308 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B28 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B147) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs